In vitro and In vivo Antifungal Activity of Alkanna tinctoria against Trichophyton rubrun and Trichophyton Mentagrophytes: Antifungal activity of Alkanna tinctoria against Trichophyton rubrun, Trichophyton mentagrophytes - Saghafi, Mohammad Mehdi; Behi, Fatemeh; Lotfali, Ensieh; Vosoogh, Mehran; Kreft, Samo; Fattahi, Mahsa (Iranian Journal of Pharmaceutical Sciences, 2021)
This study was conducted to investigate the antifungal properties of Alkanna tinctoria extracts against Trichophyton rubrum (PTCC5143), and Trichophyton mentagrophytes (PTCC 5054), and two archived clinical isolates of T. rubrum and T. mentagrophyte. Two reference strains, including T. rubrum (PTCC5143), and T. mentagrophytes (PTCC 5054) (drug-sensitive reference strains), were used, along with two archived clinical isolates of T. rubrum and T. mentagrophytes, which show resistance to terbinafine or fluconazole in vitro and clinic. A topical ointment was formulated using the dried extract of A. tinctoria (20%) roots, Vaseline, beeswax, and sesame oil. The ethanolic and aqueous extracts were prepared from the ointment and assessed for antifungal activity. In vivo antidermatophytic activity of A. tinctoria (20%) ointment was examined in six male Sprague Dawley rats infected by T. mentagrophytes. According to the results, both ethanolic and aqueous extracts showed growth inhibition against tested strains. Moreover, all strains were susceptible to amphotericin B (MIC≤0.5 μg/ml). The lowest fungistatic and fungicidal activities were exhibited by the MIC and MFC values of ethanol extract (both with 0.0125 mg/ml) against T. mentagrophytes, as well as the aqueous extracts against T. rubrum. The application of A. tinctoria (20%) ointment on the rats shortened the complete cure of T. mentagrophytes infection to 7 days compared to the 21-day complete cure using terbinafine. In the present study, A. tinctoria showed significant antifungal properties against clinical isolates of dermatophytes with resistance to azoles and terbinafine. Therefore, it can be considered a promising antifungal agent.